Tingkat Pengetahuan Tentang Karang Gigi Karang Taruna Dusun Sengir Sumberharjo Prambanan Sleman - Noor Annisa Ekawati; Taadi Taadi; Marjana Marjana (Poltekkes Kemenkes Yogyakarta, 2017)
The one causes of the problem appearing in society dental and oral health are knowledge factor in the purity of dental and oral. The knowledge class is some indications that were gotten by the human through sensory and will appear when human used the sensory or the mind. The aim of the research is to know the knowledge level about calculus at a youth organization in Sengir Sumberharjo Prambanan Sleman. The data collection method used questioner with 25 questions. The data collection of this research used saturated sample technic. The research result that had been done was mostly of youth organization member had the good knowledge about calculus as much as 85%, the knowledge level of calculus in youth organization based on the age is about the age between 14-19, 20-25, 26-30 is disposed to have good knowledge level. The knowledge level of calculus in youth organization based on the gender was, the male had good knowledge 52%. The knowledge level of calculus in youth organization based on the last education was the education stage of SLTA (Senior High School) had the knowledge level as much as 30%. The knowledge level of calculus in youth organization based on the job was, the student had a good knowledge of 47,5%. Based on the research of result can be concluded that the knowledge level of calculus at a youth organization in Sengir Sumberharjo Prambanan Sleman includes in the good category.